1994
DOI: 10.1007/bf01476482
|View full text |Cite
|
Sign up to set email alerts
|

Posterior cruciate ligament (PCL) reconstruction-an in vitro study of isometry

Abstract: Isometric positioning of the posterior cruciate ligament (PCL) graft is important for successful reconstruction of the PCL-deficient knee. This study documents the relationship between graft placement and changes in intra-articular graft length during a passive range of motion of the knee. In eight cadaveric knees the PCL was identified and cut. The specimens were mounted in a stabilising rig. PCL reconstruction was performed using a 9-mm-thick synthetic cord passed through tunnels 10 mm in diameter. Three dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…The PM graft showed relatively constant length and tension pattern between 0°and 90°of flexion. This finding concurs with the data of previous reports suggesting that the most isometric region of the PCL graft is within the small posterioroblique fibre [26,35]. For this reason, tensioning the PM graft between 0°and 90°could be acceptable.…”
Section: Discussionsupporting
confidence: 92%
“…The PM graft showed relatively constant length and tension pattern between 0°and 90°of flexion. This finding concurs with the data of previous reports suggesting that the most isometric region of the PCL graft is within the small posterioroblique fibre [26,35]. For this reason, tensioning the PM graft between 0°and 90°could be acceptable.…”
Section: Discussionsupporting
confidence: 92%
“…23,24 In conventional single-bundle PCL reconstruction, it is recommended that femoral graft fixation be placed in the so-called most isometric point. [25][26][27] However, the normal PCL consists of a posteromedial bundle that is tight in extension, and a stronger anterolateral bundle that is mostly taught in flexion. 28,29 Recent reports have demonstrated the biomechanical superiority of a double-bundle versus a single-bundle PCL reconstruction in restoring normal knee laxity.…”
mentioning
confidence: 99%
“…3,13,15,24,28,35,37 The majority of the studies found that a shallow graft will tense as the knee is flexed, and a deep graft will slacken as the knee is flexed. 3,15,31,35 However, Stone et al 38 found that the tension of a deep graft remained nearly constant over the entire range of motion. This conflicting finding may be attributed to the location of the tunnel center used by Stone et al Their tunnel may be centered shallower within the femoral footprint than the deep bundles of other studies, and a shallower center would increase the bundle's ability to resist posterior translation in flexion.…”
Section: Discussionmentioning
confidence: 99%
“…The question of where to place a one-bundle or two-bundle PCL graft to restore the complex behavior of the PCL still remains unanswered. Odensten and Gillquist, 26 Friederich et al, 10 and Petermann et al 31 have advocated isometric reconstructions; however, the isometric region comprises only a small portion of the ligament. Pearsall et al 30 reconstructed seven cadaveric knees with one-bundle bone-patellar tendon-bone grafts and reported that the isometric reconstruction restored posterior tibial translation limits from 0° to 45° but not at higher flexion angles.…”
mentioning
confidence: 99%